Environmental impact assessment of second life and recycling for LiFePO4 power batteries in China. (15th July 2022) - Wang, Yixuan; Tang, Baojun; Shen, Meng; Wu, Yizhou; Qu, Shen; Hu, Yujie; Feng, Ye
Abstract: The number of spent lithium-ion batteries (LIBs) will increase exponentially in the coming decade with the retirement of electric vehicles (EVs). There is a knowledge gap in assessing the environmental impact of different terminal disposal paths for EV LIBs in China. Here, we take representative lithium iron phosphate (LFP) power batteries as example and carry out a bottom-up life cycle assessment (LCA). The life cycle stages of battery manufacturing, use, second life and battery recycling are considered to conduct a cradle-to-grave environmental impact analysis. To investigate the environmental benefits of end-of-life (EoL) stage for LFP batteries, two EoL management scenarios are considered in this study. The first one combines second life application with battery recycling, and the second recycles the retired batteries directly after EV use. The result shows that the secondary application of retired LFP batteries in energy storage systems (ESSs) can effectively reduce the net environmental impact of LIB life cycle, especially for fossil fuel depletion. When the service life of secondary use is increased from 1 year to 10 years, the environmental benefits of different impact categories will increase by 0.24–4.62 times. For direct recycle scenario, recycling retired LFP batteries can save more than 30% of metal resources. By comparison, we find that recycling lithium nickel manganese cobalt oxide (NCM) batteries has greater environmental benefits than recycling LFP batteries for all impact categories. When considering the environmental benefits at the EoL stage, most life cycle environmental impact is likely to be offset or even show positive benefits if more than 50% of power batteries can be reused in ESSs after retirement. Graphical abstract: Image 1 Highlights: LCA under different EoL scenarios in China is conducted for EV LFP batteries. The reuse of LFP batteries are more environmentally friendly for energy storage. Environmental benefits of recycling LFP batteries are smaller than NCM batteries. Recycling methods differ significantly in environmental benefits of LIBs recycling. Some impact categories are likely to be offset if more LFP batteries are reused.